Faktor Yang Mempengaruhi Kecemasan Pada Remaja SMA Yang Akan Melaksanakan Ujian Nasional - Kita, Made Rania Artyanti; Wilani, Ni Made Ari (Peneliti.net, 2024)
Anxiety is a state when an individual feels anxious, uncertain, afraid of reality or perceived as a threat from an unknown source. This paper aims to provide information about the factors that cause anxiety in adolescents who will take the national exam, because many teenagers experience anxiety before the national exam. This paper uses a descriptive method by taking a literature review approach to previous research. The search was carried out using Google Scholar, Neliti and Garuda with journal publications in 2012-2022. Factors that cause anxiety in adolescents who will take national exams include social support, introverted and extroverted personality types, single parents, gender, anxiety traits, internal and external aspects, age and coping responses, family factors, social factors and institutional factors. Anxiety is a natural psychological condition when individuals experience anxiety, therefore social support is needed from both family and peers to increase attention to individual adolescents who are experiencing anxiety